[OP.7A.11] CHROMOGRANIN A AS A PREDICTIVE MARKER OF SUCCESSFUL RENAL DENERVATION. (September 2017) - Chamoux, N. Barber; Eikelis, N.; Pereira, B.; Hering, D.; Marusic, P.; Lambert, E.; Schlaich, M.; Lambert, G.; Esler, M.
Abstract : Objective: The reported variability in the BP response to renal denervation (RDN) has limited its clinical application. A selection of inappropriate patient cohorts (pathophysiology failure) and the inability to confirm that sufficient renal denervation has actually been achieved (technical failure) represent major obstacles. Here, we aimed to assess whether changes in the plasma concentration of chromogranin A (ChrA), a sympathetic nerve vesicular protein, could predict the blood pressure response to RDN. Design and method: Thirty one consecutive patients with resistant hypertension (65% males, age 61.7 ± 1.7 years, mean ± SEM) who underwent RDN (Symplicity® catheter) were included in this study. We analysed plasma concentrations of ChrA by ELISA. Samples from renal vein and renal artery were taken prior to (T0) and immediately after (T1) RDN. Associations between ChrA concentrations and venous and arterial noradrenaline (NA) concentrations, as well as NA spillover were analysed. Automated office systolic (SBP) and diastolic blood pressure (DBP) measurements were obtained before (T0) and 3 months (M3) after RDN using the Omron HEM-907 monitor. Results: Office BP decreased significantly at M3: SBP: 166.9 ± 3.95 vs 149.8 ± 5.43 mmHg (p = 0.0001), DBP: 89.9 ± 3.06 vs 84.5 ± 3.4 mmHg (p = 0.0045). Arterial ChrA at T0 was correlated with the change in SBP from baseline to M3 (T0-M3) (r = 0.45, p = 0.015). At T0, the arterio-venous ChrA gradient was correlated with SBP change (r = 0.43, p = 0.02). At T1, this gradient was correlated with SBP (r = 0.38, p = 0.04) and DBP change (r = 0.34, p = 0.066). The delta (T0-T1) arterial ChrA was inversely correlated with the DBP change at M3 (T0-M3) (r = −0.50, p = 0.006) but not with SBP. No correlation was found for NA and NA spillover with blood pressure change. These results suggest: 1) higher arterial ChrA concentrations at baseline predicted a more pronounced BP decrease in response to RDN, 2) an increase of ChrA after RDN, potentially explained by the release of the ChrA contained in sympathetic axons, predicted the DBP decrease. It means that an acute change of ChrA could help to confirm the success of the procedure. Figure. No caption available. Conclusions: ChrA might represent a predictor of BP response to RDN at M3. Further studies are needed to confirm these results.